Practical mobile forensics : dive into mobile forensics on iOS, Android, Windows, and BlackBerry devices with this action-packed, practical guide /: dive into mobile forensics on iOS, Android, Windows, and BlackBerry devices with this action-packed, practical guide. (2014) - Unknown
No abstract available